Biological response to an experimental implant for tibial tuberosity advancement in dogs: A pre-clinical study. (February 2020) - Plyusnin, Artem; Kulkova, Julia; Arthurs, Gareth; Jalava, Niki; Uppstu, Peter; Moritz, Niko
Abstract: In this study, we propose a novel bioresorbable bioactive implant for tibial tuberosity advancement (TTA). The implant consists of a gradually resorbing load-bearing shell which encompasses rapidly resorbing small casings loaded with silica-based bioactive glass (BG) particulates which promote bone formation and reduce the risk of infection. The shell and the casings are manufactured by 3D printing from two medical grade bioresorbable polymers (a polyglycolide/lactide based and a polydioxanone based) that have different degradation rates. The casings are expected to resorb within days after surgery to expose the BG particulates while the shell would retain the load-bearing properties of the implant for the time required by bone healing. Unlike the currently used metallic devices, the novel implant is resorbed and excreted from the body once its purpose is fulfilled. This study presents a logical progression from the in vitro characterisation of the materials and implants to the in vivo investigation of the experimental implants. This included mechanical testing of the materials, finite element analysis of a preliminary design of the novel TTA implant, assessment of the degradation behaviour of the polymers and the ion exchange of BG in simulated body fluid, and investigation of the biological response to the novel implants after implantation in rabbits. The osteointegration of the novel implants was comparable to the osteointegration of Ti6Al4V implants in the control group; the biological efficacy and safety were confirmed. The biological response was in line with the expectations. The proof of concept for the novel TTA implants was demonstrated. Highlights: Bioactive filler sealed within the novel implant can interact with the host body. The degradation rates of the implant parts can be adjusted by selection of materials. The novel implant is successfully integrated into bone with no adverse reactions. The novel implant can eventually be entirely resorbed in the host body. The proof of concept for the novel implant has been successfully demonstrated.